Study on Lipid Profile in Offspring of Dyslipidemic Parents - Azad, MKH; Hussain, SS; Choudhury, MBK; Mowsumi, FR (Journal of Dhaka National Medical College & Hospital, 2012)
As dyslipidemia is responsible for remarkable cause of cardiovascular disease which is considered as the number one cause of death globally, this study was undertaken to evaluate the lipid profile status of offspring of dyslipidemic parents in comparison with the offspring of normolipidemic parents. In this study, carried out on 89 subjects, the mean total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL-c) and low density lipoprotein (LDL-c) were 162.18 ± 20.97, 168.98 ± 33.51, 39.09 ± 3.62 and 90.41 ± 18.64 mg/dl respectively in adolescents with parental dyslipidemia and 158.38 ± 12.67, 157.22 ± 15.06, 40.51 ± 2.90 and 86.42 ± 12.39 mg/dl respectively in control adolescents. There were significant differences (p < 0.05) of TG and HDL-c between cases and controls where HDL-c choesterol was significantly lower in offspring of dyslipidemic parents then the offspring of normolipidemic parents. The findings of this study reflect the association of offspring dyslipidemia with parental dyslipidemia, probably due to some genetic predisposition. Offspring of dyslipidemic parents have higher levels of TC, TG, LDL-c and lower level of HDL-c compared to age and sex matched control subjects. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12191 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 37-40